Geographic Distribution of Avirulence Genes of the Rice Blast Fungus Magnaporthe oryzae in the Philippines - Ana Liza C. Lopez; Christian Joseph R. Cumagun; Tapani Yli-Matilla (MDPI, 2022)
A total of 131 contemporary and 33 reference isolates representing a number of multi-locus
genotypes of Magnaporthe oryzae were subjected to a PCR test to detect the presence/absence of
avirulence (Avr) genes. Results revealed that the more frequently occurring genes were Avr-Pik
(81.50%), Avr-Pita (64.16%) and Avr-Pii (47.98%), whereas the less frequently occurring genes were
Avr-Pizt (19.08%) and Avr-Pia (5.20%). It was also laid out that the presence of Avr genes in M. oryzae
is strongly associated with agroecosystems where the complementary resistant (R) genes exist.
No significant association, however, was noted on the functional Avr genes and the major geographic
locations. Furthermore, it was identified that the upland varieties locally known as “Milagrosa” and
“Waray” contained all the R genes complementary to the Avr genes tested.